Proceduralism, Political Embeddedness and Death Penalty Lawyers in China. (29th January 2019) - Lu, Hong; Trejbalova, Tereza; Liang, Bin
Abstract: Research suggests that cause lawyers are a diverse group. Death penalty lawyers with attachment to political institutions and a strong commitment to procedurals tend to have a unique path to professional identification, participation in the legal process and acquiring the ability to affect case outcomes. Borrowing from Hilbink's typologies and Liu and Halliday's analytical framework, this study examines in detail the practices of proceduralist and progressive elite lawyers. It uses a high-profile capital case, the Nian Bin case, as a case study to analyse the motivation and strategies of the lead defence lawyer in the context of progressive proceduralist cause lawyers. Relevant theoretical and policy implications as well as suggestions for future studies are discussed. 摘要: 法社会学研究表明事业律师有多种类型。死刑案件代理律师通常会因为对政治机构的依赖性，或对程序的信奉和恪守，而形成独特的职业特质，法律程序的参与度，以及锻造有效推进案子的能力。本文借鉴 Hilbink, 和刘思达和 Hallliday 的分析模式，对注重程序的改革精英派律师进行深入分析。以念斌案为案例，本文着重剖析念斌律师的动力，策略，和改革程序派律师的职业特征。文章结尾总结了该分析对相关的理论及政策的意义并提出对将来类似研究的建议。